EVALUATION OF THE ATHLETIC PERFORMANCE DEVELOPMENT PROGRAM OF THE NORTH SUMATRA NATIONAL PARALYMPIC COMMITTEE (NPC) ATHLETES AT THE XVII NATIONAL PARALYMPIC GAMES (PEPARNAS) 2024 - Afika Dwi Yulanda; Atikah Rahayu; Rifky Riyandi Prastyawan; Duwi Kurnianto Pambudi; Rina Yuniana (SOSIOEDUKASI, 2026)
This study was motivated by the decline in medal achievements at the XVII National Paralympic Games (PEPARNAS) in 2024 compared to the previous PEPARNAS. The purpose of this study was to evaluate the athletic performance development program of the North Sumatra National Paralympic Committee (NPC) athletes at the XVII PEPARNAS 2024 using the CIPP evaluation model. This evaluation study employed a quantitative approach using a questionnaire as the research instrument. The data were analyzed using percentage calculations based on the Likert scale assessment criteria. The findings revealed that the context aspect achieved 77.98% according to the administrators, 74.40% according to the coaches, and 78.38% according to the athletes. The input aspect obtained 66.67% according to the administrators, 66.67% according to the coaches, and 66.85% according to the athletes. The process aspect achieved 75.52% according to the administrators, 70.83% according to the coaches, and 72.83% according to the athletes. Meanwhile, the product aspect obtained 62.50% according to the administrators, 68.75% according to the coaches, and 68.00% according to the athletes. Based on these findings, it can be concluded that the athletic performance development program of the North Sumatra National Paralympic Committee (NPC) is categorized as good and feasible to be continued. However, special attention should be given to the input aspect to optimize the implementation of the performance development program for future PEPARNAS events.